Synthesis of ZSM-5/Siliceous Zeolite Composites for Improvement of Hydrophobic Adsorption of Volatile Organic Compounds - Li, Renna; Chong, Shijia; Altaf, Naveed; Gao, Yanshan; Louis, Benoit; Wang, Qiang (Frontiers in Chemistry, 2019)
In this research, we investigated the hydrophobicity and dynamic adsorption-desorption behaviors of volatile organic compounds (VOCs) by applying different optimized coating dosage (25, 50, and 75%) on designed novel ZSM-5/MCM-41 and ZSM-5/Silicalite-1 hierarchical composites. The relatively large specific surface area and pore volume of adsorbents ZSM-5/MCM-41 and ZSM-5/Silicalite-1 composites with excellent stability were affirmed by ex-situ XRD, FTIR, BET, SEM, and water contact angle analyses. Regarding, toluene adsorption-desorption investigation, ZSM-5/MCM-41 composite lead a longer stable toluene breakthrough time no matter under dry or 50% humid conditions. However, under different loading dosage condition, the breakthrough time of 75% coating ratio was the longest, which was 1.6 times as long as that of pure ZSM-5 under wet adsorption. Meanwhile, the complete elimination of toluene for ZSM-5/MCM-41-75% was done by largest desorption peak area and the lowest desorption temperature of 101.9°C, while, the largest contact angle of ZSM-5/MCM-41-75% was 17.0° higher than pure ZSM-5 zeolite. Therefore, we believe that the present hydrophobic sorbent will provide new insight with great research potential for removing low concentration of VOCs at industrial scale.